OSCC MAMPU OSS case study awards 2010: E-Meeting System in International Islamic University Malaysia - Ahlan, Abdul Rahman; Arshad, Yusri (MYGOSSCON, 2010)
IIUM E-meeting was first promulgated in 2004 to cater for the increasing needs of the university for an integrated scheduling and managing all meetings held by especially senate boards initially. Previously, all meetings were manually organised such as invitation to all relevant stakeholders, sharing of meeting documents, feedbacks and comments and others. The senate board, realising the benefits that can be derived from information technology, had asked the senate committee to work on a proposal to automate a system specifically for use by the senate secretariat, board and stakeholders for the senate meetings purposes.